KEANEKARAGAMAN SUKU LEJEUNEACEAE (HEPATICAE, LUMUT HATI) DI D AERAH SEKITAR PPKAB (PUSAT PENDIDIKAN DAN KONSERVASI ALAM BODOGOL) TAMAN NASIONAL GUNUNG GEDE-PANGRANGO, JAWA BARAT - Haerida, Ida (Research Center for Biology-Indonesian Institute of Sciences, 2009)
As many as thirteen species of Lejeuneaceae occurs in Bodogol, Gunung Gede-Pangrango National Park, West Java. Those species are Archilejeunea planiuscula (Mitt.) Steph., Cheilolejeunea ceylanica (Gootsche) R.M. Schust & Kachnoo, Cheilolejeunea trapezia (Nees) Kachroo & R.M. Schust., Cololejeunea denticulata (Horik.) Hatt., Cololejeunea goebeli (Gott. ex Schiffn.) Schiffh., Cololejeunea spinosa (Horik.) Hatt., Drepanolejeunea tkwaitesiana (Mitt.) Steph., Lejeunea discreta Lindenb., Lejeunea rotundistipula (Steph.) Hatt., Lejeunea sordida (Nees) Nees, Leptolejeunea maculata (Mitt.) Schiffn., Lopholejeunea subfusca (Nees) Schiffn., and Thysananthus retusus (Reinwardt, Blume & Nees) B. Thiers & Gradstein. Four species of these have not been reported previously from the island. Those are Cololejeunea denticulata, Drepanolejeunea thwaitesiana, Lejeunea rotundistipula and Cololejeunea spinosa.Keys, descriptions and figures are given for all species.